La conservazione di interi nuclei documentali. Un diverso approccio alla conservazione e al restauro. Il caso della Biblioteca di scienze sociali di Firenze Il caso della Biblioteca di scienze sociali di Firenze - Giovanna, Cestone; Conigliello, Lucilla (Proceedings e report, 2018)
In 2012, the bindings of the books of the ancient fund of the Library of social sciences showed the first signs of deterioration, due to the heavy changes in temperature and humidity of the conservation environment. While the University worked at implementing a new air conditioning system, the Tuscany Region and the officials of the National Central Library of Florence developed a project for the safety of the entire fund, to slow down the process of deterioration and prevent or stabilize the damage already present. The innovative method implemented in the Library was illustrated in a seminar held on November 24, 2016 at the Polo di Scienze Sociali of the University of Florence and this volume collects the speeches of the participants.